Impact of Student-Run Free Clinic Participation on Medical Student Attitudes Towards the Underserved: A Mixed-Methods Approach - Michael Enich; Meagan Hawes; Paul Lavadera; Karen Wei-Ru Lin (Journal of Student-Run Clinics, 2021)
Background: Student-run free clinics provide an opportunity to shape medical student practices with and attitudes towards the medically underserved. Previous literature has shown mixed results on how student attitudes change over the course of medical education. The purpose of this mixed-method study is to determine the effect that participation in a student-run free clinic has on medical student attitudes towards the underserved as compared to attitudes of non-participating students.Methods: The validated Medical Attitudes Towards the Underserved (MSATU) survey was administered in cross-sectional study to student participants in a student-run free clinic and to non-participating medical students (n = 122). Additionally, first and fourth year participant students were interviewed via semi-structured interviews about results.Results: There was no statistically significant difference in overall MSATU scores between participant and non-participant medical students using Mann Whitney tests. In sub-score analyses, Mann Whitney tests demonstrated significantly higher scores among participants in the total services score (U = 1344.0, df = 115, p = 0.013) and the expensive procedures services sub-score (U = 1401.0, df = 115, p = 0.019). Interviews revealed that positive attitudes towards the underserved are not specific to student-run free clinic participants. Participants did not describe changes in their attitude from clinic participation, believing all medical students had a baseline positive attitude towards the underserved. They did, however, highlight that witnessing the reality of these patients influenced their perspective and future practice.Conclusions: There were limited significant differences in MSATU survey scores between participant and non-participant students. Interview results suggest that the survey tool was unable to capture changes in the perspectives of participant medical students or the changes in their projected practices but that, participation in a student-run free clinic had an overall positive effect on understanding of the barriers to care and empathy towards the underserved.